Інституційне забезпечення фінансової інфраструктури : шляхи зменшення уразливості - Глущенко, Ольга Вікторівна; Glushchenko, Olga Victorivna (Київ : ТОВ "Редакція журналу `Економіка та держава", 2017)
Розкрито стан інституційного забезпечення фінансової інфраструктури шляхом аналізу державного регулювання та саморегулювання. Встановлена гиперрегуляція фінансової інфраструктури державними регуляторами та інституційна дисфункція саморегулівних організацій. На підставі дослідження динаміки зміни кількості фінансових установ доведено входження фінансовою інфраструктурою у стан інституційного регресу. Розраховано показник фінансової глибини, що відображає здатність забезпечити потреби у наданні фінансових ресурсів інститутами фінансової інфраструктури та уразливість фінансової системи. Дістало подальшого розвитку розкриття причин зростання уразливості фінансової системи, що обумовлені порушенням фінансової архітектоніки та полягають у обмеженні інституційної забезпеченості можливостей руху фінансових потоків, що веде до домінування спекулятивного та Понці-фінансування за рахунок зменшення забезпеченого типу залучення фінансових ресурсів.

This article explores the current state of institutional support of the financial infrastructure of Ukraine, its institutional organization and problems of operation. The state of institutional support of the financial infrastructure was determined by analyzing government and self-regulation. There were also determined hyper regulation of the financial infrastructure by state regulators and institutional dysfunction of self-regulating organisations. On the grounds of the dynamics of the changing number of financial institutions we proved the institutional regression of the financial infrastructure. There was also estimated the indicator of financial depth that reflects the ability to meet the needs of financial institutions in financial resources as well as financial infrastructure fragility of the financial system. Further analysis was given to the reasons for financial system fragility caused by abuse of financial architectonics and restriction of financial provision of financial flows leading to the dominance of speculative and Ponzi-funding at the cost of secured attraction of financial funds.
Institutional support of financial infrastructure : ways to reduce fragility
Keywords: SOCIAL SCIENCES::Business and economics::Economics; фінансова інфраструктура; фінансова глибина; уразливість фінансової системи; фінансова архітектоніка; фінансове посередництво; financial infrastructure; financial depth; financial system vulnerability; financial architecture; financial intermediation